2014
DOI: 10.1007/s10709-014-9797-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variability to explore the relationship complexity of Schizothoracine (Teleostei: Cyprinidae)

Abstract: Despite numerous studies on the taxonomy of a highly complex group of schizothoracine (snow trouts), with over five recognized species from Kashmir, India (Schizothorax niger, Schizothorax esocinus, Schizothorax plagiostomus, Schizothorax curvifrons and Schizothorax labiatus) based on traditional morphological data, the relationships between these species is poorly understood and the taxonomic validity is still under debate. To resolve the evolutionary relationships among these species, we sequenced mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…In the current study, two mitochondrial genes were used to validate the fish species using a binary approach, such as phenotypic and genotypic data in order to resolve the ambiguity among six important fish species of the Poonch River. A combined analysis of mitochondrial loci mostly agrees with morpho taxonomical studies (Silas, 1960;Ahmad et al, 2014), indicating that the integrative method could effectively resolve uncertainty in the identification and understanding of morphological relationships even with a low sample size. Therefore, molecular phylogenies and phenotypic studies can be compared using standard methods to come up with a robust conclusion.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In the current study, two mitochondrial genes were used to validate the fish species using a binary approach, such as phenotypic and genotypic data in order to resolve the ambiguity among six important fish species of the Poonch River. A combined analysis of mitochondrial loci mostly agrees with morpho taxonomical studies (Silas, 1960;Ahmad et al, 2014), indicating that the integrative method could effectively resolve uncertainty in the identification and understanding of morphological relationships even with a low sample size. Therefore, molecular phylogenies and phenotypic studies can be compared using standard methods to come up with a robust conclusion.…”
Section: Discussionsupporting
confidence: 70%
“…No work has been reported on these fish species from this water body; however, little work has been reported from other water bodies in the region and other parts of the country (Ahmad et al, 2014;Jaafar et al, 2021), revealing the ambiguity among Schizothorax and Tor genus. But the current study is different from the previous ones (Ahmad et al, 2014) as they focused on the single genus of Schizothorax, but here we Frontiers in Genetics frontiersin.org have adopted an integrative approach to five different genera, including Schizothorax and Tor as well, in a single attempt. Ghouri et al (2020) reported the efficiency of Cyt b for the identification of edible fish species in Pakistan.…”
Section: Molecular Analysis (Cyt B + 16s Rrna)mentioning
confidence: 83%
See 2 more Smart Citations
“…In current investigation, sequences of C. catla follow the neutral evolution (R ¼ .5), while C. mrigala (R ¼ 2.01) and L. rohita (R ¼ 2.84) deviated from it due to external mutations. Such type of deviation was also observed in Schizothoracinae (Ahmad et al 2014;Akhtar and Ali 2016). Examination of CO1 gene of all three species, Catla, Labeo and Mrigala, illustrated very low genetic diversity (<.55) which may be caused by factors such as minimum rate of evolution, decrease in long-term survival, incomplete lineage sorting, inbreeding due to the small size of population, reduced adaptation and fitness (DeSalle and Amato 2004;Frankham 2009).…”
Section: Combined (Three Fish Species) Sequences Analysesmentioning
confidence: 70%